Applying typological insights in a minority-language context: Motion event lexicalisations in Ladin, Italian, German and English texts compiled by Ladins - Irsara, Martina (Glottodidactica, 2020)
This paper investigates the lexical choices made by speakers of Ladin in describing the opening scene of Mayer’s (1969) Frog, where are you? in Ladin and in the other languages they learnt later in life (Italian, German and English). The focus of the investigation is on motion lexicalisation, which varies across languages in terms of preferred encoding patterns (Talmy 1985, 2000; Wälchli 2001). Relative frequencies are calculated for the variants occurring in the different languages, before turning to a qualitative discourse-analytic approach, which forms the core of the analysis. The results are discussed with reference to the fields of typology and cross-linguistic research. The analysed texts bring to the fore the necessity of distinguishing between national and regional idioms and the potential value of drawing cross-linguistic issues to the explicit attention of learners. Possible implications are considered with reference to the novel framework of Applied Language Typology (Filipović 2018).